COAL DE-ASHING BY SOLVENT EXTRACTION - Datin Fatia Umar; Fahmi Sulistyohadi; Gandhi Kurnia Hudaya (Indonesian Mining Journal, 2015)
Coal contains mineral matter that will be left as ash after coal is burned. Coal will be referred to as dirty coal if the ash content of the coal is high. High ash content is not preferred by consumers of coal users especially coal fired power plants, because ash content will produce fly ash and bottom ash that cause environmental problem. The process of ash content reduction by solvent extraction would produce coal with very low ash content (near zero) known as ash free coal (AFC). The study of ash content reduction was conducted by using Peranap coals that were taken from stockpile and mine site. The coals were then washed and separated into coals with low and high ash contents. The high ash content of coals from stockpile (46.02%) and mine site (25.02%) were then extracted using solvent. Three kinds of solvent have been tested, namely 1-methyl naphthalene, 1-1-1-methoxy ethoxy acetic acid and N-methyl 2 pyrolidynon. The results indicate that the ash content of coal derived from the stockpile decreased to 0.06% and coal from the mine site decreased to 0.11% by using 1-methyl naphthalene solution with a ratio of coal and solvent of 1: 6 (weight/weight).